Safety data on in situ gelling bimatoprost loaded nanovesicular formulations - Monika Yadav; Ana Guzman-Aranguez; Maria J. Perez de Lara; Mandeep Singh; Joga Singh; Indu Pal Kaur (Data in Brief, 2019)
In vitro cytotoxicity and in vivo acute and 7 days repeat-dose ocular toxicity studies, were conducted in rabbits, in accordance with the Organisation for Economic Co-operation and Development (OECD) guidelines, for bimatoprost loaded nanovesicular aqueous dispersion (BMT-NV) and its in-situ gelling sub-conjunctival implant (BMT-NV-IM). For details on the preparation and evaluation of BMT-NV and its BMT-NV-IM for the control of glaucoma, please refer to ‘Bimatoprost loaded nanovesicular long-acting sub-conjunctival in-situ gelling implant: In vitro and in vivo evaluation’ (Yadav et al., 2019). The in vivo ocular toxicity was performed only after confirming dermal safety, as required by OECD. Histological evaluation of various ocular tissues, following sub-conjunctival implantation with BMT-NV-IM, was done for ocular tolerance studies. Keywords: Cytotoxicity, Ocular toxicity, In situ gelling, Acute and repeat dose toxicity, Sub-conjunctival implants, Cell lines